An Analysis of the Main Drivers for ISO 9001 and other Isomorphic Metastandards - Iñaki HERAS-SAIZARBITORIA; Germán ARANA; Eduardo SAN MIGUEL (Revista de Management Comparat International)
Research on the adoption of metastandards (e.g. ISO 9001, ISO 14001, OHSAS 18001, SA 8000) has used a variety of theoretical perspectives to identify the main driving forces or motivations. While the majority of existing studies on this subject are of an empirical character with little development of a theoretical framework, there are nonetheless a certain number of noteworthy studies undertaken in the context of a clear and consistent conceptual and theoretical framework, on the basis of which various working hypotheses may be assessed and compared. In this article the main theoretical perspectives for the analysis of the motivations for the adoption of metastandards are reviewed. Furthermore, a short review of the empirical literature dealing with the drivers for ISO 9001, the most promiment metastandard, is carried out, in order to shed light on this issue for both the researchers and practitioners interested in this management tool.